Pemberian Scaffolding untuk Meningkatkan Kemampuan Representasi Matematis Siswa dalam Menyelesaikan Masalah Matematis Berdasarkan Resiliensinya: Providing Scaffolding to Improve Students' Mathematical Representation Ability in Solving Mathematical Problems Based on Their Resilience - Eva Fitria Ningsih; Binti Khusnul Chotimah; Sastika Astridewi (ITScience (Information Technology and Science), 2025)
The background of this research problem is based on students' mathematical representation ability and mathematical resilience being relatively low. To address this problem, a study was conducted by providing scaffolding in their learning. The purpose of this study was to see the improvement of students' mathematical representation ability based on their resilience with the provision of scaffolding. The method used in this study was a quasi-experimental design with two different treatments given to the experimental and control classes. Class VII A became the experimental class, where learning was given treatment using the scaffolding process. Class VII B became the control class, where no treatment was given (regular learning). Students in the experimental and control classes were grouped first based on their mathematical resilience categories. The instruments used were a mathematical representation ability test and a mathematical resilience questionnaire. Data analysis used the Two-Way ANOVA statistical test. Based on the results of the Two-Way ANOVA statistical test, the class factor has a sig of 0.000 <0.05, meaning that H0 is rejected, the mathematical resilience factor has a sig of 0.001 <0.05, meaning that H0 is rejected, and the interaction factor between class and mathematical resilience has a sig of 0.000, which results in H0 being rejected. Based on the results of the research data analysis, there s a difference in the increase in mathematical representation abilities of students who receive scaffolding in their learning compared to those who receive regular learning. When viewed based on the categories of high, medium, and low mathematical resilience, there is a difference in the increase in mathematical representation abilities. Furthermore, there is also an interaction between learning with the scaffolding process and students' mathematical resilience in influencing the increase in students' mathematical representation abilities.